A high strength and high electrical conductivity bulk CuCrZr alloy with nanotwins. (1st April 2015) - Sun, L.X.; Tao, N.R.; Lu, K.
Abstract : A bulk nanostructured CuCrZr alloy consisting of nanotwins and nanograins was prepared by dynamic plastic deformation at liquid nitrogen temperature. A tensile strength of 700 MPa and an electrical conductivity of 78.5% International Annealed Copper Standard are obtained in the nanostructured CuCrZr alloys processed by means of this one-step deformation without aging treatment. The reason for the increased strength without the sacrifice of its high electrical conductivity was discussed.